2020
DOI: 10.1007/978-3-030-58799-4_43
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Ensemble Methods for Predicting Train Delays

Abstract: Train delays have become a serious and common problem in the rail services due to the increasing number of passengers and limited rail network capacity, so being able to predict train delays accurately is essential for train controllers to devise appropriate plans to prevent or reduce some delays. This paper presents a machine learning ensemble framework to improve the accuracy and consistency of train delay prediction. The basic idea is to train many different types of machine learning models for each station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This means that their method would not generalise well. In a previous study [31] we showed that heterogeneous ensembles outperformed random forest for predicting train delays. The motivation of this research is to help improve the UK train network by developing an accurate and reliable machine learning ensemble by efficiently combining multiple models generated from different standard learning algorithms into a heterogeneous ensemble.…”
Section: Work In Related Fieldsmentioning
confidence: 92%
“…This means that their method would not generalise well. In a previous study [31] we showed that heterogeneous ensembles outperformed random forest for predicting train delays. The motivation of this research is to help improve the UK train network by developing an accurate and reliable machine learning ensemble by efficiently combining multiple models generated from different standard learning algorithms into a heterogeneous ensemble.…”
Section: Work In Related Fieldsmentioning
confidence: 92%